Effect of Pepper Stem Fiber Orientation on Mechanical Properties, Water Absorption, and Biodegradation of Cassava Bioplastic Films - Irwan Ramli; Fahri Alfito; Hilda Rahmawati (Journal of Physics and Its Applications, 2026)
Plastic pollution continues to pose a serious environmental challenge due to the persistence of petroleum-based polymers in ecosystems. Starch-based bioplastics offer a biodegradable alternative; however, their practical application is limited by low mechanical strength and high water absorption. This study investigates the effect of pepper stem waste fiber (Piper nigrum) reinforcement and fiber orientation (aligned vs. random) on the mechanical properties, water absorption, and biodegradation behavior of cassava starch films. Bioplastic films were prepared in three formulations: control (without fibers), aligned fiber reinforcement (AFR), and random fiber reinforcement (RFR). Structural and performance evaluations were conducted using X-ray diffraction (XRD), tensile testing, water absorption analysis, and soil burial biodegradation (8 cm depth). XRD patterns confirmed semi-crystalline starch structures with characteristic peaks at 2θ ≈ 17°, 19°, and 22°. Tensile strength increased from 0.6957 MPa (control) to 0.7873 MPa (AFR), corresponding to a 13.2% improvement, indicating enhanced load transfer in aligned fiber structures. Water absorption decreased from 70% (control) to 50% (RFR), showing a 28.6% reduction, likely due to increased tortuosity of water diffusion pathways. Soil burial testing showed rapid degradation, reaching 28.37% mass loss by day 3 and 100% mass loss/disintegration by day 6 under the tested conditions. Overall, pepper stem fibers improve the performance of cassava starch films while maintaining rapid biodegradability, highlighting their potential for environmentally friendly disposable and packaging applications.